THE IMPLEMENTATION OF THE PHONICS METHOD TO ENHANCE THE YOUNG LEARNERS’ ENGLISH PRONUNCIATION - Riska Furining Tiyas; Asfi Aniuranti; M.Happy Nur Tsani; Siti Khalimah (Economics, Social, and Humanities Journal (Esochum), 2023)
The purpose of this study is to foster pupils' abilities in English pronunciation. Participants in this Classroom Action Research (CAR) were the students of sixth grade in MI Ma'arif NU Sunyalangu consisting of 20 students. Their English pronunciation abilities were still considered low because the pretest average score was only 48.86. The tools used were the test questions and the observation sheet. In order to enhance their English pronunciation skills, the researchers utilized the Phonics method. This method was chosen due to its merits in teaching English pronunciation. Two cycles of study were undertaken. The average score on the posttest for cycle 2 was 85.69, which was higher than the successful criteria of this study (65). In short, the phonics method could help pupils pronounce English more clearly, especially young learners.